PENGELOLAAN ARSIP SURAT MASUK DAN ARSIP SURAT KELUAR PADA BIRO UMUM DAN PERLENGKAPAN SEKRETARIAT DAERAH PROVINSI SULAWESI SELATAN - Anne Abdul Rachman (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2022)
An abstranct is a brief summary of a research article, thesis, review, conference proceeding or Management of incoming and outgoing mail archives is an important activity that must be carried out by an agency. Correspondence activities must get serious attention, because the contents of the letter to the agency will be a means of achieving the goals of the agency, therefore it is necessary to have good mail management in a company or agency. Therefore, the government issued Governor Regulation Number 1 of 2011 concerning the management of dynamic archives, mail management must be developed by means of information technology and developed into a means of regional government office administration system. The purpose of this study is to describe the management of incoming and outgoing mail archives at the General Bureau and Equipment for the Regional Secretariat of Sulawesi Province. The research approach used is descriptive qualitative and is supported by secondary data. The type of data used is primary data obtained from interviews and secondary data obtained from data processing and observation. The data analysis technique starts from collecting information through interviews and at the final stage by drawing conclusions. The results showed that the management of incoming and outgoing mail archives at the General Bureau and Equipment of the Regional Secretariat of South Sulawesi Province had not run effectively and efficiently, where the management of outgoing mail had not been running properly, which was caused by facilities and infrastructure factors as well as unsupporting human resources.